Frequency of Dental Injuries in Patients Reporting to the Armed Forces Institute of Dentistry - Rana, Nadeem Ahmed; Abbasi, Qurat ul Ain; Maryum, Dr Areeba; Ullah, Mohib; tu Zahra, Syeda Fatima; Yousaf, Ajmal (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the frequency, cause and type of dental injury in patients reporting to Armed Forces Institute of Dentistry.Study design: Cross-Sectional Survey.Place and Duration of Study: Department of Operative Dentistry Armed Forces Institute of Dentistry, Rawalpindi, Pakistan, from Sep 2021 to Sep 2022.Methodology: A questionnaire was filled out for 357 patients reporting dental injury, including the extent of hard and soft tissue injuries. The cause and place of injury occurred; investigations, the treatment provided by the treating dentists ranging from restoration to root canal, type and duration of splint were also recorded.Results: In the current study, 189(52.9%) out of 357 children got injury due to falls to the playground and other places. Maxillary incisors were mostly affected, and 163(45.7%) children had complicated crown fractures. Rigid splinting was done in 39(70.9%) of root fracture cases, while flexible splinting was done in 162(53.6%) patients with complicated crown fracture cases and 81(26.8%) complicated crown fracture cases. In 72(88.8%) cases of uncomplicated crown fracture, indirect pulp capping was done, and in 67(41.1%) cases of complicated crown fracture, root canal treatment were done. Apexification was done in 28(68.3%) of avulsion cases.Conclusion: Our survey showed that most injuries occurred at school and the roadside. Maxillary incisors are primarily involved with complicated crown fractures, which are effectively managed.Keywords: Avulsion, Complicated crown fracture, Dental injury, Splinting.